THE NEED OF SPATIAL TYPOLOGIES IN TOURISM PLANNING AND POLICY MAKING - THE GREEK CASE - Harry Coccossis; Mary Constantoglou (European Regional Science Association (ERSA), 2005)
Greek tourism has been developed since the 70's. Main scope of this development was the economic support of areas with rich natural and cultural capital. This process has created a number of effects (positive and negative ones) at the destination areas mainly because of the lack of integrated planning. The necessity for tourism planning in local, regional and national scale is obvious, especially when the main objective is the preservation and the competitiveness of the destination areas. Tourism development is differentiated from place to place and tourism policy must reflect that. A spatial typology for tourism development is necessary in order to develop sharper policy measures. In this paper we will examine a spatial typology that has been created for the Greek coasts for policy making.
Keywords: 330